Wireless Networks and Security: Issues, Challenges and Research Trends - Khan, Shafiullah; Pathan, Al-Sakib Khan (Springer, 2012)
First of all, we would like to express our solemn gratitude to the “Almighty Allah” for giving us time and keeping us fit for work to timely complete this arduous project. Thanks to the authors from different countries who have contributed to the book, also thanks to those authors whose manuscripts we have not been able to include due to the rigorous review-based selection process. The final outcome has come out with total 14 chapters in total ranging various issues on wireless network security.